Leaflet Based Education and Its Effect on the Level of Knowledge of Adolescent Girls Regarding Mental Health - Fatmasari, Baiq Dika; Ernawati, Ernawati; Wirastri , Dwi (Ahmar Metastasis Health Journal, 2025)
Mental health among adolescent girls is a crucial aspect in supporting optimal emotional, social, and academic development. The complex biological, psychological, and social changes that occur during adolescence increase vulnerability to stress, anxiety, and depression. One promotive and preventive effort that can be implemented is health education using leaflet media, which is simple, informative, and easy to understand. This study aimed to analyze the effect of leaflet-based education on the level of knowledge of adolescent girls regarding mental health at SMAN 1 Wanasaba. This study employed a quantitative pre-experimental design using a one-group pretest–posttest approach. The study population consisted of all eleventh-grade female students, with a sample of 60 respondents selected through simple random sampling. Data were collected using a structured questionnaire to measure the level of mental health knowledge before and after the leaflet-based educational intervention. Data analysis was conducted using the Wilcoxon test. The results showed an increase in the level of knowledge among adolescent girls after receiving leaflet-based education. The Wilcoxon test indicated a statistically significant difference between knowledge scores before and after the intervention (p < 0.05). These findings indicate that leaflet-based health education is effective in improving adolescent girls’ knowledge regarding mental health.